PENGARUH KEDISIPLINAN DAN KEPEMIMPINAN TERHADAP MOTIVASI KERJA DAN KINERJA GURU SMP NEGERI 1 PIYUNGAN - ., Tugiman (STIE AUB Surakarta, 2014)
The purpose of this study was to determine empirically the influence of discipline and leadership on teacher motivation and performance of SMP N 1 Piyungan Bantul. The data used in this study was primary data were taken with a list of questions given to all teachers, as many as 55 respondents. Test instrument used, path analysis, t test, F test, test R2, and the linearity test. The test results showed all instruments were valid and reliable. T test results can be concluded that the discipline and leadership variables had positive and significant impact on the motivation and performance. Simultaneously test results jointly independent variables affected performance. From the test results obtained R2 value was 0.876, which means the performance was explained by the discipline and leadership to work motivation as an intervening variable was 87.6% and the remaining 12.4% was explained by other variables did not study such a work environment, job satisfaction. Direct and Indirect influence: The direct effect of discipline on the coefficient of performance was greater than the indirect effect on performance through motivation discipline. The direct effect of leadership on performance was greater than the coefficient of the indirect effect on performance through motivational leadership. Motivation can be concluded to be ineffective as an intervening variable. Keywords: discipline, work discipline, motivation, performance